2022
DOI: 10.3390/en15041252
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Ensemble Methods Using Machine Learning and Deep Learning for One-Day-Ahead Forecasts of Electric Energy Production in Wind Farms

Abstract: The ability to precisely forecast power generation for large wind farms is very important, since such generation is highly unstable and creates problems for Distribution and Transmission System Operators to properly prepare the power system for operation. Forecasts for the next 24 h play an important role in this process. They are also used in energy market transactions. Even a small improvement in the quality of these forecasts translates into more security of the system and savings for the economy. Using two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…However, both the averaged and accumulated ET 0 predicted by SVR models were much closer to the real observations than did the linear regression models. In previous studies, Piotrowski et al found that the SVR model had higher prediction accuracy than linear regression models, such as the ridge regression model [46]. Moreover, among those linear regression models, the Bayesian regression model had higher accuracy than the other two proposed linear models.…”
Section: Forecast Performance Of Single Modelsmentioning
confidence: 97%
“…However, both the averaged and accumulated ET 0 predicted by SVR models were much closer to the real observations than did the linear regression models. In previous studies, Piotrowski et al found that the SVR model had higher prediction accuracy than linear regression models, such as the ridge regression model [46]. Moreover, among those linear regression models, the Bayesian regression model had higher accuracy than the other two proposed linear models.…”
Section: Forecast Performance Of Single Modelsmentioning
confidence: 97%
“…Forecasts for the next 24 h are used in energy market transactions. Even small improvements in their quality translate into greater system security and savings for the economy [35]. Recently, algorithms based on deep learning such as long short-term memory (LSTM) [36] or convolutional neural networks [37] have also been used for energy forecasting over different time horizons.…”
Section: Artificial Intelligence Algorithms In Energy Forecastingmentioning
confidence: 99%
“…These problems are then addressed by many researchers, where we can mention [ 48 ], who presented a dynamic prediction of retail electricity prices in the Smart Grid based on the Stackelberg model. Then, [ 49 ], where the authors discuss the possibility of using ML and DL in refining the power generation forecast, and similarly [ 50 , 51 , 52 ] discuss the stability and security of the Smart Grid concerning short-term load. In conclusion, Smart Grids are rapidly replacing conventional grids on a global scale.…”
Section: Cyber Security In Substation Automation Systemsmentioning
confidence: 99%